Efektivitas Pajak Daerah dalam Meningkatkan Pendapatan Asli Daerah: Bukti Empiris Kabupaten Bantul - Riska Yuanita Indriyani; Erlinda Nur Khasanah (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This study aims to examine the impact of local taxes, including Land and Building Tax for Rural and Urban Areas (PBB-P2), Duty on the Acquisition of Land and Building Rights (BPHTB), and Groundwater Tax (Ground Water Tax/PAT) on Local Own-Source Revenue (PAD).Method: This study uses a quantitative approach with secondary data in the form of PBB, BPHTB, PAT, and PAD revenue realization data for the 2020-2023 period. The total sample consisted of 48 samples. The research hypothesis was tested through multiple regression analysis using SPSS 26.Finding: The results show that PBB-P2, BPHTB, and PAT have a positive and significant impact on Bantul Regency's PAD.Novelty: There are still inconsistencies in the results of previous research, which indicate that there are research discrepancies that require further study, especially in the context of regions with different economic characteristics and tax potential.